PENGARUH EDUKASI GIZI TERHADAP PEMAHAMAN ISI PIRINGKU PADA SISWA MI 1 JELUN: THE EFFECT OF NUTRITION EDUCATION ON UNDERSTANDING OF THE ISI PIRINGKU IN STUDENTS OF MI 1 JELUN - Arsila Khabibi; Nazwa Aulia; Syarifa Gadis Venaprilla; Septa Indra Puspikawati (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2026)
Introduction: Indonesia still faces complex nutritional problems, one of which is caused by the low public understanding of balanced nutrition. Elementary school children, especially grades 3 and 4, are a vulnerable group that requires educational interventions to shape healthy eating behaviors. The concept of